2019
DOI: 10.3389/fpsyt.2019.00488
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Quantitative Checklist for Autism in Toddlers in an Italian Clinical Sample of Young Children With Autism and Other Developmental Disorders

Abstract: Background: The Quantitative Checklist for Autism in Toddlers (Q-CHAT) is parent-report screening questionnaire for detecting threshold and sub-threshold autistic features in toddlers. The Q-CHAT is a dimensional measure normally distributed in the general population sample and is able to differentiate between a group of children with a diagnosis of autism and unselected toddlers. Objectives: We aim to investigate the psychometric properties, score distribution, and external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Moreover, at 18 months, these last two clusters of the I-TC, combined with item 20 of the Q-CHAT, constitute a model of three predictors with very high sensitivity and specificity. This confirms that the I-TC is a broadband screener which covers multiple developmental areas while the Q-CHAT seems more specific for autism and better discriminates among autism children, typical development and also from other developmental conditions, as suggested by Ruta et al [25].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, at 18 months, these last two clusters of the I-TC, combined with item 20 of the Q-CHAT, constitute a model of three predictors with very high sensitivity and specificity. This confirms that the I-TC is a broadband screener which covers multiple developmental areas while the Q-CHAT seems more specific for autism and better discriminates among autism children, typical development and also from other developmental conditions, as suggested by Ruta et al [25].…”
Section: Discussionsupporting
confidence: 84%
“…The top-performing SVM model reached an overall accuracy of 95% with a sensitivity and speci city of 90% and 100% respectively, compared to RF (sensitivity=85% and speci city=95%) and NB (sensitivity=82% and speci city=100%). If we compare these results with those obtained applying the standard ROC analysis to the same participant sample [13], we found that ML algorithms were able to improve the classi cation accuracy of the Q-CHAT. In the previous study [13], the ROC curve showed an accuracy of 89.5% (vs. 95%), sensitivity = 83% (vs. 90%) and speci city = 78% (vs. 100%).…”
Section: Discussionmentioning
confidence: 91%
“…If we compare these results with those obtained applying the standard ROC analysis to the same participant sample [13], we found that ML algorithms were able to improve the classi cation accuracy of the Q-CHAT. In the previous study [13], the ROC curve showed an accuracy of 89.5% (vs. 95%), sensitivity = 83% (vs. 90%) and speci city = 78% (vs. 100%). Furthermore, by running the SVM-RF algorithm, we were able to select a sub-group of 14 items which maintained a very high accuracy, sensitivity and speci city (93%, 87% and 96% respectively for SVM).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For these reasons, the EFA estimating the two-factor structure was preferred and reached a moderate fit of the data, χ 2 (1651) = 2940.15, p < 0.001, CFI = 0.79, RMSEA = 0.034 (LO90% = 0.032, HI90% = 0.036). Nineteen items (Items 4,5,6,16,(27)(28)(29)31,32,39,41,(49)(50)(51)(52)(53)(54)(55)(56) were excluded from the subsequent analysis because the factor loadings loaded for two or more factors. After exclusion of those items, the subsequent fourth EFA reached moderate fit of the data, χ 2 (739) = 1185.47, p < 0.001, CFI = 0.92, RMSEA = 0.03 (LO90% = 0.027, HI90% = 0.033).…”
Section: Internal Consistency and Factorial Analysesmentioning
confidence: 99%